2013
DOI: 10.1523/jneurosci.5133-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Inhibition Rescues Chronic Cognitive Deficits Induced by Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) modulates several cell signaling pathways in the hippocampus critical for memory formation. Previous studies have found that the cAMP-protein kinase A signaling pathway is downregulated after TBI and that treatment with a phosphodiesterase (PDE) 4 inhibitor rolipram rescues the decrease in cAMP. In the present study, we examined the effect of rolipram on TBI-induced cognitive impairments. At 2 weeks after moderate fluid-percussion brain injury or sham surgery, adult male Sprague Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 85 publications
0
70
0
Order By: Relevance
“…Pharmacological suppression of PDE4 activity promotes synaptic plasticity and memory (Randt et al, 1982;Barad et al, 1998;Rutten et al, 2009;Werenicz et al, 2012). The PDE4 selective inhibitor, rolipram, prevents memory deficits associated with sleep loss (Vecsey et al, 2009), traumatic brain injury (Titus et al, 2013), aging (Wimmer et al, 2012), muscarinic or NMDA receptor blockade (Egawa et al, 1997;Wiescholleck and Manahan-Vaughan, 2012), and mouse models of Alzheimer's disease (Gong et al, 2004;Reneerkens et al, 2009;Richter et al, 2013). However, the clinical use of broad PDE4 inhibitors is limited due to undesirable side effects, including emesis and diarrhea (Zeller et al, 1984;Bertolino et al, 1988;Spina, 2008).…”
Section: Significance Statementmentioning
confidence: 99%
“…Pharmacological suppression of PDE4 activity promotes synaptic plasticity and memory (Randt et al, 1982;Barad et al, 1998;Rutten et al, 2009;Werenicz et al, 2012). The PDE4 selective inhibitor, rolipram, prevents memory deficits associated with sleep loss (Vecsey et al, 2009), traumatic brain injury (Titus et al, 2013), aging (Wimmer et al, 2012), muscarinic or NMDA receptor blockade (Egawa et al, 1997;Wiescholleck and Manahan-Vaughan, 2012), and mouse models of Alzheimer's disease (Gong et al, 2004;Reneerkens et al, 2009;Richter et al, 2013). However, the clinical use of broad PDE4 inhibitors is limited due to undesirable side effects, including emesis and diarrhea (Zeller et al, 1984;Bertolino et al, 1988;Spina, 2008).…”
Section: Significance Statementmentioning
confidence: 99%
“…Both clinical and experimental studies have shown that hippocampal neurons are particularly vulnerable to TBI, and loss of these neurons can continue for weeks to months after moderate-to-severe TBI. 12,13 The link between hippocampal neuronal damage and memory impairments has been established both in human TBI patients and in rodent TBI models using hippocampal-dependent learning and memory tasks. [14][15][16] However, no clinically proven neuroprotective therapy to reduce neuronal damage and improve learning and memory has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…MeCP2 was initially characterized as a methyl-DNA binding protein (Lewis et al, 1992) and a suppressor of gene transcription (Nan et al, 1997). Consistent with this notion, the majority of RTT-causing mutations are found in either the methyl-CpG binding domain or the transcription repression domain (Samaco and Neul, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…To further elucidate the molecular mechanism underlying the cellular phenotypes of abnormal neuronal morphology and mitochondrial deficit in MECP2 mutant neurons, we focused on CREB, a transcription factor known to indirectly regulate MeCP2 level (Klein et al, 2007), directly interact with MeCP2 (Chahrour et al, 2008), and control the expression of numerous genes that regulate dendritic growth (Redmond et al, 2002;Wayman et al, 2006) and mitochondrial function (Ryu et al, 2005). Western blot analysis revealed significantly reduced levels of both total CREB and phosphorylated CREB (pCREB, a signature of CREB activation) in MECP2 T158M/T158M and MECP2-KO neurons compared with H9 neurons (Fig.…”
Section: Reduced Creb Level Underlies Defects In Neuronal Growth and mentioning
confidence: 99%
See 1 more Smart Citation